2021
DOI: 10.1039/d1ce01055g
|View full text |Cite
|
Sign up to set email alerts
|

Separation of a diastereomeric diol pair using the mechanical properties of crystals

Abstract: We report the separation of visually indistinguishable acicular morphologies of (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair based on their mechanical responses, which is found to be more efficient than conventional separation methods....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…31,32 Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate 33 and (2S,3R)-3ethyl-1-phenylhex-5ene-2,3-diol. 34 The methodologies based on hydrogen bonding are still far more useful and general compared to those based on halogen bonding, π−π interactions, etc. Understanding the role of strong−weak interactions in governing molecular motions and further utilizing both types of interactions to design different mechanically flexible crystals are of paramount importance, and it will make searching for new examples easier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate 33 and (2S,3R)-3ethyl-1-phenylhex-5ene-2,3-diol. 34 The methodologies based on hydrogen bonding are still far more useful and general compared to those based on halogen bonding, π−π interactions, etc. Understanding the role of strong−weak interactions in governing molecular motions and further utilizing both types of interactions to design different mechanically flexible crystals are of paramount importance, and it will make searching for new examples easier.…”
Section: Introductionmentioning
confidence: 99%
“…These soft molecular crystals share properties of both crystals and soft matter, endowing them with great potential in mechanical actuators, optical devices, organic electronics, etc. The mechanical properties of molecular crystals strongly rely on the molecular packing arrangements and intermolecular interactions, which can be tailored by crystal engineering approaches. Designing new structures with the desired physical and chemical properties using advanced third-generation strategies of crystal engineering is an attractive and rapidly developing research area. , Much effort has been made to study the mechanism of flexible crystals and gain a deep understanding of mechanical compliance to a large extent. The importance of weak dispersive interactions has been acknowledged as it has a natural advantage in controlling local molecular movements, which is essential to ensure the effective dissipation of stresses generated from structural functions. Almost all of the key structures of mechanically flexible crystals exhibit a combination of weak intermolecular interactions such as van der Waals (vdW), weak hydrogen-bonding, , lighter halogen, ,, and π···π interactions. , Several recent studies reported unusual plastic crystals based on strong hydrogen bonding. , Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate and (2 S ,3 R )-3-ethyl-1-phenylhex-5ene-2,3-diol . The methodologies based on hydrogen bonding are still far more useful and general compared to those based on halogen bonding, π–π interactions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several cases have been reported that demonstrate that the mechanically plastic crystals can be obtained based on strong hydrogen bonding, 21,22 involving the elusive role of the solvent molecule. Gamidi et al 23 obtained elastic crystals based on the strong-weak hydrogen bonding interactions. Almost all of the elastic cases are based on aromatic organic molecular crystals 15,24 and, to the best of our knowledge, only metal salt nonaromatic systems 25 and cyclohexanol derivatives 26 have been reported up to now.…”
mentioning
confidence: 99%